Tale of Loss & Personal Ruin in Response to Time of Crisis in Selected Plays by Christopher Shinn & Jon Robin Baitz - Misbah, Randa Abdelfattah Mohamed (European Scientific Journal, ESJ, 2019)
Dying City by Christopher Shinn, an American playwright, premiered at the Royal Court Theatre in London 2006. Other Desert Cities by Jon Robin Baitz, also an American playwright, premiered at Off-Broadway in January 2011. Both plays deal with Iraqi war in apolitical way. However, Dying City puts into focus conflicting identities as a result of social and political context that threatens individuals’ agency and concepts about themselves. Meanwhile, Other Desert Cities investigates domineering paternal relationships that produce passive/docile subjects. This study demonstrates that individuals’ agency and identity could be affected by domination relationship, limiting individuals’ choices and eliciting rebellion. This is undertaken by investigating characters’ ability to resist hegemonic relationships and endure controversial war debate. Characters’ subordination and resistance are also discussed. However, Shinn and Baitz’s aims are not to deal with the war but to underline its influence on personal relationships.